Observational study of quality of life in patients with headache, receiving homeopathic treatment - Muscari-Tomaioli, G; Allegri, F; Miali, E; Pomposelli, R; Tubia, P; Targhetta, A; Castellini, M; Bellavite, P (British Homeopathic Journal, 2001)
This study describes the results obtained from a prospective observational research of homeopathic treatment for patients suffering from headache (migraine with- and without aura and tension-type headache). Fifty-three patients were asked to complete the SF-36 questionnaire at the beginning of the treatment and after 4–6 months. The homeopathic medicine and potency were not pre-defined, but were adapted to each single patient according to individualised homeopathic prescription. Most patients (73.6%) completed the study. There was heterogeneity in the answers (patients in very poor health as well as those with only slight disorders). Analysis of the data according to the concept of ‘intention-to-treat’ showed that after therapy, the mean and median scores of all life quality dimensions rose. More than 60% of the cases experienced an improvement in pain and the limitations caused by pain, as well as in limitations in social activities and health in general. All the differences between pre/post treatment were statistically highly significant, with the strongest results in the ‘bodily pain’ and ‘vitality’ parameters (P<0.0001).
Keywords: cephalalgia; migraine; observational study; prospective study; homeopathy; clinical research methods; quality of life